The Effectiveness of The Principle of Consumer Recognition from Bank in Preventing The Crime of Money Laundering - Rafii Diaz Rasendriya; Aidul Fitriciada Azhari (Proceeding International Conference Restructuring and Transforming Law, 2023)
This journal entitled "Effectiveness of the Principle of Getting to Know Consumers from Banks in Preventing the Crime of Money Laundering" focuses on research to determine policy arrangements for implementing the principle of getting to know consumers in the series of preventing criminal acts of money laundering through banking transactions. The problem in this writing is how to apply the principles regarding consumers in banking transactions and the obstacles encountered by banks in implementing the principles regarding consumers in banking transactions. Based on the problems that have been prepared, it can be concluded that in implementing the principles regarding consumers from banks in order to avoid criminal acts of money laundering, banks are obliged to implement principles regarding consumers continuously and significantly by implementing five basic elements, namely organizational policies, clear policies and procedures regarding consumer acceptance, provisions for ongoing updates and surveys on customer accounts and transactions, provisions for documenting files and reports of suspicious financial transactions, as well as risk management policies and internal regulations. Then, in implementing the principle provisions regarding consumers, all parties must be active in their implementation, both from the banking sector and the people who use banking services.